2012
DOI: 10.1080/19942060.2012.11015402
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Explicit Modelling of Watersheds with Urban Drainage Systems

Abstract: ABSTRACT:In rainfall-runoff modelling of urbanized and semi-urbanized watersheds, the urban drainage systems considerably influence runoff propagation time. In small scale watersheds, the drainage network may be modelled explicitly. In contrast, for larger watersheds, most hydrological models are based on a rough representation of the effects of drainage systems, thus failing to represent the rapidly-varying real flow dynamics. Therefore, a trade-off methodology has been developed to account for impervious sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Our analysis shows that the effect of increased impervious surface on ecohydrologic processes, specifically transpiration and NPP, is a function of not only total area but also the connection between impervious surface and the drainage network. Our ecohydrologic results parallel empirical and modeling studies that link stream hydrograph responses to urbanization—to both the total impervious area and fraction of connected impervious area [ Alley and Veenhuis , ; Walsh and Kunapo , ; Dewals et al ., ]. Here we demonstrate that by reducing the EIA fraction and explicitly accounting for disconnections between impervious surface and the stream, the reductions in total hillslope scale T and NPP associated with increased impervious area and vegetation loss are substantially less.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Our analysis shows that the effect of increased impervious surface on ecohydrologic processes, specifically transpiration and NPP, is a function of not only total area but also the connection between impervious surface and the drainage network. Our ecohydrologic results parallel empirical and modeling studies that link stream hydrograph responses to urbanization—to both the total impervious area and fraction of connected impervious area [ Alley and Veenhuis , ; Walsh and Kunapo , ; Dewals et al ., ]. Here we demonstrate that by reducing the EIA fraction and explicitly accounting for disconnections between impervious surface and the stream, the reductions in total hillslope scale T and NPP associated with increased impervious area and vegetation loss are substantially less.…”
Section: Discussionmentioning
confidence: 77%
“…Recently, Dewals et al . [] have investigated the impact of differentiating between drained (effective) and undrained surfaces when modeling storm events over a larger catchment and found that accounting for the faster routing of water from drained surfaces improved model predictions of peak quick flow. The sensitivity of model output to fine‐scale impervious surface characteristics over a longer (seasonal or multiyear) time scale has not yet been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…This metric captures connectivity and extent of impervious surfaces. Modeling studies have shown that EI predicts runoff volumes and storm event peak discharges well (Dewals et al, ; Guo, ; Lee & Heaney, ; Palla & Gnecco, ; Schoener, ; Shields & Tague, ). However, there is currently a lack of empirical studies examining the watershed‐scale effects of connectivity to SCMs on water quality, and only a few modeling studies exist (Jefferson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Urban streams experience increases in low flows when inputs from leaky water supply pipes and sewers migrate to the stream between storm events but also experience decreases because impervious surfaces reduce infiltration, the water table level, and therefore rates of groundwater flow entering the stream (Bhaskar et al, 2016). While the extent of urban impervious surfaces is an important control on watershed hydrology, the hydrologic connectivity of these surfaces to stream networks through constructed drainage channels and storm sewers also controls peak discharge and runoff volume (Alley & Veenhuis, 1983;Bell et al, 2016;Dewals et al, 2012;Shields & Tague, 2014;Shuster et al, 2005;Walsh et al, 2005;Walsh & Kunapo, 2009). These drainage networks cause runoff, rich in nutrients like nitrogen (N), to bypass biologically active zones in both the terrestrial and riparian environments, which limits the ability of urban ecosystems to remove or retain excess nutrients that enter the watershed by atmospheric deposition, imported food (subsequently released as wastewater), and applied fertilizer (Bernhardt et al, 2008;Duncan et al, 2013;Groffman et al, 2004;Hatt et al, 2004;Kaushal & Belt, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…An original procedure based on Lagrange multipliers is applied to simulate river junctions. The model was used in a number of previous hydrological studies, such as Dewals et al (2012) andKhuat Duy et al (2010). Regular cell sizes of 200 m were used to discretize the whole river network.…”
Section: Hydrological Model and Flow Routingmentioning
confidence: 99%